Cecal Duplication Cyst Presenting as an Intussusception: A Case Report - Rizalar R.; Somuncu S.; Demirag F.; Gurses N. (My University, 1993)
A case of ileocolic intussusception due to cystic duplication of the caecum in a 8 months old girl is presented. A review of the literature reveals the extreme rarity of this entity.
Keywords: Duplication Cyst; Intussusception